Applications of RNA interference high-throughput screening technology in cancer biology and virology. Issue 11 (22nd June 2014) - Gao, Shan; Yang, Chen; Jiang, Shan; Xu, Xiao-Ning; Lu, Xin; He, You-Wen; Cheung, Annie; Wang, Hui
Abstract: RNA interference (RNAi) is an ancient intra-cellular mechanism that regulates gene expression and cell function. Large-scale gene silencing using RNAi high-throughput screening (HTS) has opened an exciting frontier to systematically study gene function in mammalian cells. This approach enables researchers to identify gene function in a given biological context and will provide considerable novel insight. Here, we review RNAi HTS strategies and applications using case studies in cancer biology and virology.